PENGARUH PENILAIAN KINERJA TERHADAP MOTIVASI KERJA, DISIPLIN KERJA DAN LOYALITAS KERJA PENDAMPING PKH DI UPPKH KABUPATEN KEDIRI - Nurhasan Nurhasan (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
The purpose of this research is to know the influence of performance appraisal against the work motivation, work discipline and work Loyalty of pendamping Program Keluarga Harapan (PKH) Regency Kediri separately. With the research on the influence of performance appraisal against job motivation, discipline and loyalty escort work as well as its impact on Unit Pelaksana Program Keluarga Harapan (UPPKH) District of Kediri. The population in this research is the entire Regency Kediri PKH escort a number of 100 people. In this study all companion became the subject of research. To analyze the problem in this research used descriptive and análisis análisis single regression method by using a data processing program with the Statistical Package for the Social Science (SPSS) 16. The results of the research and the discussion above, it can be concluded that; 1. There is a significant influence of the variable performance appraisal against the motivation of working Pendamping PKH in UPPKH Kediri Regency. With the most dominant indicator of performance appraisal variable is an indicator of the acceptability and practical. 2. There is a significant influence of the variable performance appraisal against the Disciplined Work Pendamping PKH in UPPKH Kediri Regency. With the most dominant indicator of performance appraisal variable is an indicator of reliability and practical. 3. There is a significant influence of the variable performance appraisal against Job Loyalty Pendamping PKH in UPPKH Kediri Regency. With the most dominant indicator of performance appraisal variable is an indicator of the reliability and relevant.